Re‐entrant dipole glass‐like behavior and lattice dynamics of 0.65Bi(Mg1/2Ti1/2)O3‐0.35PbTiO3. Issue 4 (24th December 2019) - Chen, Kaiyuan; Wei, Fu; Jia, Liu; Tianxiang, Yan; Lan, Zhencheng; Fang, Liang; Peng, Biaolin; Wang, Dawei; Liu, Laijun
Abstract: The 0.65Bi(Mg1/2 Ti1/2 )O3 ‐0.35PbTiO3 (0.65BMT‐0.35PT) ceramic, nearby morphotropic phase boundary (MPB), between tetragonal and rhombohedral was prepared. Dielectric permittivity dependence of temperature exhibits a re‐entrance dipole glass‐like behavior near room temperature. The behavior was described by the Vogel‐Fulcher law and the new glass model . Furthermore, a phenomenological statistical model was employed to determine the distribution of clusters dependence of temperature. The lattice dynamics of the 0.65BMT‐0.35PT ceramic was estimated by Raman spectroscopy from 298‐723 K. A disruption of ferroelectric long‐range order and an occurrence of local lattice distortion were revealed. The relaxor‐ferroelectric (r‐FE) nature of the 0.65BMT‐0.35PT was characterized by polarization‐electric field P(E) . A close relation between the distribution of clusters and ferroelectric properties was established.